Chinese Rural Migrants in Urban Enterprises: Three Perspectives. - Knight, J; Song, L; Huaibin, J (Department of Economics (University of Oxford), 1997)
A suvey of rural migrants employed in enterprises in four Chinese cities is analysed. The process of migration is analysed from three perspectives: that of the rural migrants themselves, of their urban employers, and of the government. They survey results are combined with marcroeconomic projects to consider the future of migration in China.